The Consumption Behaviour of Muslim Students towards Halal Food in Yogyakarta Indonesia: A SEM Aproach - Fauzan Husaini (Global Review of Islamic Economics and Business, 2015)
Halal food is a strategic sector in Indonesia, because most of Indonesian are muslim and consumpting it is a must. This study aims to look at the main factors that influence consumption behavior of Muslim students in Yogyakarta toward halal food. In this study the analysis method used is Structural Equation Modeling (SEM) to verify the factors that determine the consumption behavior of Muslim students in DIY toward halal food. The data used is primary data derived from questionnaires with 188 respondents. The results showed that of five independent variable, only four which affect toward intention to buy halal food positively and significantly, namely religiosity factors, social factors, attitudes and perceived value, while the halal label does not affect the intention to buy halal food.